Ecological Piety: A Qur'anic Conceptual Review of Green Islamic Character Education - A. Saeful Bahri; Napsin Napsin; Zaenal Abidin; Dadang Komara; Nenden Maryati (Universitas Pendidikan Ganesha, 2025)
The environmental crisis has become an urgent global issue due to damage caused by human activities and failures in environmental management, such as improper waste handling that triggers flooding, as well as mining and industrial activities that drive ongoing climate crises. This phenomenon reflects humanity’s failure to fulfill its role as stewards (khalifah) of the earth. This study aims to analyze the concept of ecological piety from the perspective of Qur’anic exegesis and to explore its application in green Islamic character education. Employing a qualitative approach with a literature review method, this research examines classical and contemporary tafsir texts, books, and relevant scholarly articles. Data were collected through in-depth document analysis and thematically analyzed to identify key concepts and strategies for implementing environmentally conscious character education. The findings reveal that ecological piety in the Qur’an emphasizes moral and spiritual responsibility to preserve the environment as an act of worship and devotion to Allah SWT. Ecological piety needs to be integrated into Islamic education curricula to cultivate environmentally caring attitudes grounded in faith. The implications of this study encourage the development of green Islamic character education models to support the creation of environmentally aware Muslim generations who are responsible for the earth’s sustainability.